Migrant Workers’ Housing Effects on Their Urban Adaptation: An Empirical Case Study of the Wuling Mountains Area in China - Sidi, Xiao; Guang, Tian (Journal of Applied Business and Economics, 2023)
It is a unique feature of China’s urbanization and a must for migrant workers to integrate into cities. Migrant workers can be integrated into urban life quickly if their housing problem is adequately addressed. However, resolving the housing problem is one of the critical challenges in migrant workers’ urban adaptation. This paper defines an urban transformation from economic, social, psychological, and cultural dimensions and analyzes it from housing facilities, housing performance, supporting facilities, and community environment. Structural equation modeling explores the path between housing and migrant workers’ urban adaptation in the Wuling Mountains area and its impact on their urban adaptation. Then, it proposes suggestions for the government, community, enterprises, and migrant workers from different perspectives to guide the solution to migrant workers’ housing difficulties and facilitate their urban adaptation.